Laporan Observasi Sosial Emosional pada Anak Usia Dini di TK An-Nida - Maldina Aulia Rahmi; Khadijah Khadijah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to describe the socio-emotional development of early childhood students at TK An-Nida and explore the involvement of parents and teachers in supporting the process. A descriptive qualitative method was used, involving direct observation and interviews. The results show that most children are at the